2022
DOI: 10.1186/s12931-022-02222-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of upper and lower respiratory symptoms on COVID-19 outcomes: a multicenter retrospective cohort study

Abstract: Background Respiratory symptoms are associated with coronavirus disease 2019 (COVID-19) outcomes. However, the impacts of upper and lower respiratory symptoms on COVID-19 outcomes in the same population have not been compared. The objective of this study was to characterize upper and lower respiratory symptoms and compare their impacts on outcomes of hospitalized COVID-19 patients. Methods This was a multicenter, retrospective cohort study; the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…These variants have also been shown to be more sensitive to lower temperatures 72,73 . In contrast, Omicron variant viruses do not have the same sensitivity to temperature that has been observed in prior variants and have been observed to target the upper airway 72,79 . This may be due to differences in entry pathway preferences and cellular tropism 75,76,77 .…”
Section: Discussionmentioning
confidence: 84%
“…These variants have also been shown to be more sensitive to lower temperatures 72,73 . In contrast, Omicron variant viruses do not have the same sensitivity to temperature that has been observed in prior variants and have been observed to target the upper airway 72,79 . This may be due to differences in entry pathway preferences and cellular tropism 75,76,77 .…”
Section: Discussionmentioning
confidence: 84%
“…This study utilized data from the largest long COVID symptom cohort study in Japan and performed an additional analysis focusing on upper respiratory symptoms. These symptoms are predictors of mild COVID‐19 10,11 . Three upper respiratory symptoms were often comorbid during hospitalization; however, over time, sore throat resolved and disappeared, while taste and olfactory disorders were comorbid at 12 months in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Taste and olfactory disorders are commonly associated with an initial COVID‐19 diagnosis during the acute phase 5‐8 ; however, they can persist as part of long COVID 9 . At the onset of COVID‐19, upper respiratory symptoms, including sore throat, taste disorders, and olfactory disorders, have been identified as predictors of mild disease severity 10,11 . These symptoms are also frequently reported among individuals experiencing long COVID 3,4,12‐15 .…”
mentioning
confidence: 99%
“…Previous studies have also linked lower respiratory infection during COVID-19 infection with negative outcomes. A 2022 study found that COVID-19 patients with lower respiratory symptoms experienced worse health outcomes, including supplemental oxygen, mechanical ventilation, and death, compared to patients with upper respiratory symptoms or no respiratory symptoms (18). Lower respiratory infection during acute COVID-19 may be a causal pathway by which acute COVID leads to PASC, although future studies should apply a causal inference framework to evaluate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%